1988
DOI: 10.1002/jts.2490010108
|View full text |Cite
|
Sign up to set email alerts
|

Helping families of homicide victims: A multidimensional approach

Abstract: Homicide inflicts massive injury upon the intrapsychic and interpersonal realities of thesurviving kin of murder victims. A New York City pilot program of outreach and counselling to 1182 families of Brooklyn homicide victims suggests that surviving kin undergo the symptoms of traumatic stress disorder. Recovery is prolonged by knowledge that the perpetrator is usually alive and in some cases unpunished, by repetitive con frontations with the criminal justice system and by the multiple losses endured: loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 5 publications
2
35
0
Order By: Relevance
“…Further research is required to ascertain the impact of socioeconomic and ethnic variables on survivor adjustment. Related to this question, Masters et al (1988) have observed that within their Victims Services Agency in New York City, ". .…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to ascertain the impact of socioeconomic and ethnic variables on survivor adjustment. Related to this question, Masters et al (1988) have observed that within their Victims Services Agency in New York City, ". .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the responsiveness of others can help to restore the survivor's self-esteem, trust in others, and hope for a better future. On the other hand, interactions with people who are insensitive or indifferent to her suffering can impede the survivor's attempts at cognitive reconstruction (Masters, Friedman, & Getzel, 1988;Wortman & Dunkel-Schetter, 1979).…”
Section: Cognitive Processes Involved In Adaptation To Traumamentioning
confidence: 99%
“…However, some authors have suggested a category of 'traumatic grief' (Horowitz et al, 1997;Prigerson et al, 1999) to cover particularly traumatic bereavements including through homicide. Responses following traumatic bereavement include feelings of rage and a wish for revenge, the loss of belief and value system, social withdrawal and isolation, stigmatization, extreme guilt, fear and suicidal ideation (Amick-McMullan, Kilpatrick, Veronen, & Smith, 1989;Burgess, 1975;Masters, Friedman, & Getzel, 1988;Parkes, 1993;Rando, 1988;Raphael 1997;Redmond, 1990;Rynearson, 1984). The social and legal reverberations following homicide, with lack of information about the legal process, can compound and prolong the grieving process for surviving relatives (Amick-McMullan et al, 1989;Brown & Christie, 1997;Burgess 1975;Masters et al, 1988;Thompson, Norris, & Ruback, 1998).…”
mentioning
confidence: 99%